Zambia: Agricultural R&D indicators factsheet - Beintema, Nienke M.; Mumba, Rhoda; Mwala, Moses; Gao, Lang (International Food Policy Research Institute, 2016)
This country factsheet presents key agricultural R&D indicators in a highly accessible visual display. The publication also feature a more in-depth analysis of some of the key challenges that the country’s agricultural R&D system is facing, and the policy options to address these challenges.